Oxygen vacancies on Nb2O5 enhanced the performance of H2O2 electrosynthesis from O2 reduction. Issue 60 (7th July 2022) - Peng, Xiaoge; Zhang, Shijie; Bao, Zhikang; Ding, Lei; Wang, Guoliang; Shao, Yizhen; Xu, Zaixiang; Ji, Wenkai; Feng, Ge; Wang, Shibin; Zhong, Xing; Wang, Jianguo
Abstract : The presence of oxygen vacancies on the Nb2 O5 electrocatalyst increases the adsorption of oxygen and then accelerates the 2e − ORR. Abstract : A serial oxygen vacancy (OV ) on Nb2 O5 is synthesised by H2 calcination, and H-300 exhibited high selectivity and activity for H2 O2 (93.4%, 562.5 mmol gcat −1 ). A volcano relationship is identified between the OV content and performance, which provides an attractive insight into designing electrocatalysts.